In vivo uptake of a haem analogue Zn protoporphyrin IX by the human malaria parasite P. falciparum-infected red blood cells - Sartorello, Robson; Budu, Alexandre; Bagnaresi, Piero; Fernandes, Carlos A. H. [UNESP]; Sato, Paloma M.; Bueno, Vania B.; Fontes, Marcos R. M. [UNESP]; Oliveira, Pedro L.; Paiva-Silva, Gabriela O.; Alves, Simone V.; Netto, Luis E. S.; Catalani, Luiz H.; et al. (Portland Press, 2010)
The cellular traffic of haem during the development of the human malaria parasite Plasmodium falciparum, through the stages R (ring), T (trophozoite) and S (schizonts), was investigated within RBC (red blood cells). When Plasmodium cultures were incubated with a fluorescent haem analogue, ZnPPIX (Zn protoporphyrin IX) the probe was seen at the cytoplasm (R stage), and the vesicle-like structure distribution pattern was more evident at T and S stages. The temporal sequence of ZnPPIX uptake by P. falciparum-infected erythrocytes shows that at R and S stages, a time-increase acquisition of the porphyrin reaches the maximum fluorescence distribution after 60 min; in contrast, at the T stage, the maximum occurs after 120 min of ZnPPIX uptake. The difference in time-increase acquisition of the porphyrin is in agreement with a maximum activity of haem uptake at the T stage. To gain insights into haem metabolism, recombinant PfHO (P. falciparum haem oxygenase) was expressed, and the conversion of haem into BV (biliverdin) was detected. These findings point out that, in addition to haemozoin formation, the malaria parasite P. falciparum has evolved two distinct mechanisms for dealing with haem toxicity, namely, the uptake of haem into a cellular compartment where haemozoin is formed and HO activity. However, the low Plasmodium HO activity detected reveals that the enzyme appears to be a very inefficient way to scavenge the haem compared with the Plasmodium ability to uptake the haem analogue ZnPPIX and delivering it to the food vacuole.
Keywords: cellular traffic; confocal microscopy; haem oxygenase; malaria; Plasmodium